2020
DOI: 10.1002/pon.5439
|View full text |Cite
|
Sign up to set email alerts
|

Serial multiple mediation of demoralization and depression in the relationship between hopelessness and suicidal ideation

Abstract: Objective: Suicidal ideation is common in cancer patients and may be associated with hopelessness, demoralization, and depression. This study aims to investigate the serial multiple mediation of demoralization and depression in the relationship between hopelessness and suicidal ideation in cancer patients. Methods: A total of 244 cancer patients were investigated by using the following standardized self-reported questionnaires: self-rating idea of suicide scale, Beck hopelessness scale, demoralization scale-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…The results of the present study are consistent with a previous study 8 which identified a class reflecting poor coping without anhedonia and other classic depression symptoms, but linked to suicidal ideation. The present study is also consistent with studies showing that suicidality has stronger links with demoralisation than depression in cancer patients 4–7 . For people facing the existential threat of cancer, demoralisation symptoms with suicidal ideation, but without anhedonia, may indicate poor psychological adjustment to the stressors of their illness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the present study are consistent with a previous study 8 which identified a class reflecting poor coping without anhedonia and other classic depression symptoms, but linked to suicidal ideation. The present study is also consistent with studies showing that suicidality has stronger links with demoralisation than depression in cancer patients 4–7 . For people facing the existential threat of cancer, demoralisation symptoms with suicidal ideation, but without anhedonia, may indicate poor psychological adjustment to the stressors of their illness.…”
Section: Discussionsupporting
confidence: 91%
“…The present study is also consistent with studies showing that suicidality has stronger links with demoralisation than depression in cancer patients. 4 , 5 , 6 , 7 For people facing the existential threat of cancer, demoralisation symptoms with suicidal ideation, but without anhedonia, may indicate poor psychological adjustment to the stressors of their illness. Thus, demoralisation may be an important element of AD which contributes importantly to the independent link between AD and suicidality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, demoralization can occur independently of depression and the two conditions are not necessarily linked by a hierarchical connection [89,99,105,106]. In some cases, it has been demonstrated that demoralization had a predominant [89,97,98] or synergistic [99,100,107] effect with depression on the potentiation of SI and SB. In both cases described above, a depressive condition was suspected, and a psychopharmacological treatment was initiated.…”
Section: Psychiatric and Psychosocial Hypotheses For Suicidality Etiomentioning
confidence: 99%